2020
DOI: 10.3390/molecules25122766
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Activity and Molecular Docking of Novel Thiourea Derivatives Tagged with Thiadiazole, Imidazole and Triazine Moieties as Potential DNA Gyrase and Topoisomerase IV Inhibitors

Abstract: To develop new antimicrobial agents, a series of novel thiourea derivatives incorporated with different moieties 2–13 was designed and synthesized and their biological activities were evaluated. Compounds 7a, 7b and 8 exhibited excellent antimicrobial activity against all Gram-positive and Gram-negative bacteria, and the fungal Aspergillus flavus with minimum inhibitory concentration (MIC) values ranged from 0.95 ± 0.22 to 3.25 ± 1.00 μg/mL. Furthermore, cytotoxicity studies against MCF-7 cells revealed that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 29 publications
(54 reference statements)
1
31
0
Order By: Relevance
“…The derivatives with high AMES toxicity prediction values were found to be more toxic. [26] In this pharmacokinetics study, all the ArBTU derivatives showed hepatotoxic behavior without any skin-sensitive activity. The ADMET study proved that the ArBTU derivatives exhibited virtuous lead-like potential but slight hepatotoxic.…”
Section: Pharmacokinetics Study (Admet) Of Arbtu Derivatives (3 A-3 J)mentioning
confidence: 76%
“…The derivatives with high AMES toxicity prediction values were found to be more toxic. [26] In this pharmacokinetics study, all the ArBTU derivatives showed hepatotoxic behavior without any skin-sensitive activity. The ADMET study proved that the ArBTU derivatives exhibited virtuous lead-like potential but slight hepatotoxic.…”
Section: Pharmacokinetics Study (Admet) Of Arbtu Derivatives (3 A-3 J)mentioning
confidence: 76%
“…The biological potential of the newly prepared target structures was inspected toward the examined organisms and expressed as the diameter of the inhibition zones due to the agar plate diffusion technique. [64][65][66][67][68][69] More details in the ESI. † 2.2.5.1.…”
Section: Chemistrymentioning
confidence: 99%
“…All strains were maintained as freeze-dried stocks in reconstituted (11% w/v) skim milk, containing 0.1% w/v ascorbic acid and routinely cultivated in optimal growth conditions [35] (Table 2). These bacteria were chosen to represent the diversity of species of food-borne (labels 1-22; 31-35) and environment-borne (labels [23][24][25][26][27][28][29][30]36) Gram-positive and Gram-negative bacteria.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…A biocide is only active when it can pass through the outer layers of the cell, the structure and composition of which allows it to act as a barrier. In the literature, thiourea derivatives with antibacterial activity tested in vitro against pathogenic strains both Gram-positive ( Staphylococcus aureus, Bacillus subtilis and Bacillus cereus ) and Gram-negative ( Escherichia coli, Proteus vulgaris and Pseudomonas aeruginosa ) have been described and the results have shown considerable activity and a broad spectrum of action [ 28 , 29 ]. The presence of two thiourea moieties, as in the case of bis derivatives, is thought to have a better antibacterial activity, probably due to the fact that the C = S and NH groups of thiourea are easily protonable in acidic conditions and can react with the carboxyl and phosphate groups of the bacterial surface, thus improving the activity.…”
Section: Introductionmentioning
confidence: 99%